Pemanfaatan Lahan Pekarangan dengan Budidaya Lebah Madu Trigona di Desa Sigerongan Kecamatan Lingsar Kabupaten Lombok Barat - Sri Maryati; Sri Supartiningsih; Wuryantoro Wuryantoro; I Ketut Budastra; Taslim Sjah; Ni Made Wirastika Sari (Unram Journal of Community Service, 2022)
House yard is one of the resources that can be used for various productive activities, one of which is the business of Trigona honey bee cultivation. Trigona honey bee cultivation business provides many benefits, including honey, propolis, bee bread, all of which are very useful for public health and can also be a business opportunity. The location of community service activities is in the sub village of Jati Mekar, Sigerongan Village, Lingsar District, West Lombok Regency. The method of implementing the activities used is lecture method, discussion and practice of how to harvest honey, breaking up bee colonies and making bee bread energy drinks. The participants of the activity were the people of Jati Mekar Sub village, Sigerongan Village (youth group). The results of the activity were considered very positive, as it could increase the knowledge of the participants and the participants were motivated to do the business. The evaluation shows that the extension and practice activities are very useful in increasing public knowledge about Trigona bee cultivation, and the activities can be carried out again in the same location with continued activities or in different locations with the same theme